Long-term history of continental weathering and particle transport to the sea - Don E. Canfield; Shuichang Zhang; Ross N. Mitchell; Xiaomei Wang; Amin Naemi; Christopher J. Spencer; Pengyaun Zhang (Proceedings of the National Academy of Sciences, 2025)
Here, we explore the long-term history of chemical weathering and particle transport from the continents to the oceans by leveraging the histories of Zr/Al, Rb/Al, and Na/Al in marine sediments over the last 2000 My. We interpret these data in the context of elemental behavior in modern weathering environments and modern marine sediments. We find that from 2000 Mya to ca. 650 Mya, physical erosion was effective, where braided rivers efficiently delivered particles from land to the sea. Overall, chemical weathering was less efficient than now, although many easily weatherable minerals were as weathered as today. We suggest a dramatic change in weathering dynamics after 650 Mya when modern-like deep subduction originated. With this development, mantle dynamics, by promoting periodic vigorous subduction and intense mountain building, began to control the intensity of chemical weathering and particle transport to the oceans. Through spectral analysis of several geochemical records, we find that during times of enhanced subduction and mountain building, continents underwent periods of net erosion and less intense chemical weathering, while during periods of less intense subduction, continents accumulated particles, and chemical weathering was more intense. The evolution and proliferation of land plants changed chemical weathering intensity but had little apparent impact on the cyclic nature of particle transport and storage on the continents. These results could offer a framework to better understand the evolution of elemental cycling from the continents to the oceans over the last 2000 My.